Sometimes it also rains up: on transvestites, their loves and disaffections (2010)
Starting from stories of transvestites, a thoughtful and critical exposition is woven on how these individuals locate themselves in a heteronormative gender order while, on the other hand, they legitimate and problematize these norms in their ways of relating with themselves and others. This paper presents some of the elements that permeate the reality of transvestite prostitution, namely how they construct their gender identities, their notions of femininity and masculinity, their body, their views on love, and the roles they assume and experience in their erotic-emotional relationships